2019
DOI: 10.1017/brimp.2019.11
|View full text |Cite
|
Sign up to set email alerts
|

Measuring access to primary healthcare services after stroke: A spatial analytic approach

Abstract: Objective:To determine accessibility of the primary healthcare system for patients with stroke recently discharged from hospital.Methods:This project mapped retrospective patient location data and the location of primary healthcare services in the same region. Patient location data were from all patients with stroke (N = 1595: January 2011–January 2017) discharged from one metropolitan hospital to the local Primary Health Network. Geographic Information System technology was used to map the patient discharge l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In many disciplines, Geographic Information System (GIS)-based methodology has been widely used to assess and measure transportation accessibilities (Finch et al, 2019; Ozel et al, 2016). We utilized ArcMap 10.7.1, which is the central application used in ArcGIS.…”
Section: Methodsmentioning
confidence: 99%
“…In many disciplines, Geographic Information System (GIS)-based methodology has been widely used to assess and measure transportation accessibilities (Finch et al, 2019; Ozel et al, 2016). We utilized ArcMap 10.7.1, which is the central application used in ArcGIS.…”
Section: Methodsmentioning
confidence: 99%
“…Data from patients' electronic medical records had been used in some studies in different countries and was proven to be available for scientific research. [4][5][6][7][8][9] However, historical medical records are greatly underused in healthcare accessibility studies. One reason is due to geoprivacy issue which might hinder using historical medical record data.…”
Section: Introductionmentioning
confidence: 99%
“…Various factors may contribute to problems of service access and associated unmet needs. For example, a recent geospatial mapping study in Australia for stroke patients found that access to general practices, pharmacies and allied health services was variable according to geographical location and often substandard in non‐urban areas (Finch et al, ). Previous research on outcomes and service use after minor stroke has tended to use cross‐sectional approaches, which do not account for changes during recovery, despite recognition of the diverse and temporal nature of emotional, social and participation needs, particularly in the early post‐discharge phase (Edwards et al, ; Rozon & Rochette, ).…”
Section: Introductionmentioning
confidence: 99%